Acute appendicitis in four children with SARS-CoV-2 infection - Jessica S. Meyer; Grant Robinson; Shannon Moonah; Daniel Levin; Eugene McGahren; Katye Herring; Melinda Poulter; Linda Waggoner-Fountain; Debbie-Ann Shirley (Elsevier, 2021)
We describe 4 children (11-17 years in age) at our institution with acute appendicitis in the setting of SARS-CoV-2 infection, suggesting a possible association. Providers should consider testing for this infection in patients with severe gastrointestinal symptoms, in order to take appropriate transmission based precautions, until more is understood.